Efektivitas Peraturan Daerah Nomor 3 Tahun 2022 Tentang Larangan Berjualan Di Trotoar Taman Raja Tombolotutu Kecamatan Tinombo Kabupaten Parigi Moutong - Riska, Melan; Tahili, Mashuri H.; Moh. Royfandi (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2025)
This study aims to determine the extent to which the local regulation is effective in creating public order, especially in the Raja Tombolotutu park area, Tinombo District, Parigi Moutong Regency. The research method used is a qualitative approach with descriptive research type. Data collection techniques were conducted through interviews, observation, and documentation. This research uses the theory of measuring effectiveness from Richard M. Steers 1985 which consists of three indicators, namely goal achievement, integration, and adaptation. The results showed that the implementation of Local Regulation No. 3 Year 2022 on the prohibition of selling on sidewalks has not been effective. In the goal achievement indicator, there are still many traders who sell on the sidewalk because the location is strategic and crowded with buyers. On the integration indicator, coordination between agencies has not run optimally, limited to reporting without routine enforcement. While in the adaptation indicator, there is no concrete solution from the government for affected traders, and park management by related agencies has not been maximized.